Tingkat Kebahagiaan Migran Keluar Jakarta - Wijanarko, Andri (Jurnal Ekonomika dan Bisnis Islam, 2020)
Jakarta is the capital and largest city in Indonesia, with a population of 10,277,628 inhabitants (2016) spread over 6 regions, while the highest number of residents leaving in January to April 2018 is in the East Jakarta and West Jakarta regions. This article uses a qualitative method that uses an online questionnaire with respondents who have lived in Jakarta for 6 months who have now left Jakarta for 6 months as well. Based on the results of the study showed there was no Easterlin Paradox due to increased happiness when salaries were not fixed or decreased, but when salaries increased.